Kashin Ceramics of the Golden Horde Era from the Archaeological Settlements of the Chiyalik Culture in the Southern Urals - Evgeny V. Ruslanov (Археология евразийских степей, 2024)
In recent years, the late medieval archaeology of the Southern Urals has concentrated on the study of settlements left by the bearers of the Chiyalik archaeological culture (XIII-XIV centuries). Currently known monuments have been discovered in the forest steppe zone, mainly in the basin of the Belaya River and its left major tributaries (Ik, Urshak, Dyoma, Karmasan and Chermasan). The article considers the objects located in the central part of the Southern Urals (the territory of modern central Bashkiria and the eastern part of Tatarstan). The purpose of the work is a general analysis and classification of kashin ceramics revealed during the excavations of the Chiyalik culture settlements. The subject of study are fragments of ware found during excavations, the importance of this source of information can scarcely be exaggerated, due to its uniqueness, this type of open-type vessels, even in a fragmented state, acts as a fairly reliable chronological datum point, allowing us to outline possible trade and exchange relations.